2016
DOI: 10.1515/secm-2015-0327
|View full text |Cite
|
Sign up to set email alerts
|

Aging analysis of high voltage silicone rubber/silica nanocomposites under accelerated weathering conditions

Abstract: Silicone rubber (SiR) is extensively used in outdoor insulation and other applications. However, like other polymers, SiR also degrades and lessens its performance in the exposition of environmental stresses. Nanofillers improve the aging behavior of polymeric insulating materials. To investigate the effect of nanosilica on the aging behavior of SiR, we fabricated nanocomposites of SiR with 2.5 wt.% nanosilica (SNC-2.5) and 5 wt.% nanosilica (SNC-5) by mechanical mixing and ultrasonication method. The prepared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…S2 shows the lowest LC, making it more stable after 9000 h of aging. S2 presented improved breakdown strength (percentage loss) as compared to the samples in Yuan et al 10 In case of Khattak et al, 32 5000 h aging was performed and the obtained results indicated the improved performance of SNC-5 (silicone rubber with 5 wt% nano-SiO 2 ). The overlapping wave number presented better performance of SNC-5 as compared to the SNC-2.5 (silicone rubber with 2.5 wt% nano-SiO 2 ).…”
Section: Comparative Analysis: Critical Discussion With Recent State-mentioning
confidence: 89%
See 1 more Smart Citation
“…S2 shows the lowest LC, making it more stable after 9000 h of aging. S2 presented improved breakdown strength (percentage loss) as compared to the samples in Yuan et al 10 In case of Khattak et al, 32 5000 h aging was performed and the obtained results indicated the improved performance of SNC-5 (silicone rubber with 5 wt% nano-SiO 2 ). The overlapping wave number presented better performance of SNC-5 as compared to the SNC-2.5 (silicone rubber with 2.5 wt% nano-SiO 2 ).…”
Section: Comparative Analysis: Critical Discussion With Recent State-mentioning
confidence: 89%
“…This loss and recovery pattern in hydrophobicity was also observed by other researchers. 32,33 It can be seen from Figure 7 that SV sample losses hydrophobicity from HC1 to HC5 level. The SV sample started with a high HC3 level and then dropping to HC2 level for some time.…”
Section: Resultsmentioning
confidence: 96%
“…Putting fitting parameters of EPNC from Table 3 in (1) and solving for x . x=18,972thickmathspaceLabhours The high resistivity of silica and its good interaction at nanoscale with polymer matrix may be the reasons of increased surface resistivity which resulted in relatively less leakage current in the case of the nanocomposite [20, 21].…”
Section: Resultsmentioning
confidence: 99%
“…The thermal degradation resistance of silicone rubber is the best in all kinds of rubbers [7,8]; silicone rubber also has excellent weather resistance, aging resistance and good electrical insulating properties, which make it irreplaceable by other materials [9]. However, the mechanical properties of silicone rubber are poor [10,11]; the addition of inorganic filler, such as silica, to reinforce rubber composite systems has been researched for several decades [12][13][14][15], thus the need for further research. On the other hand, in recent years scholars at home and abroad have been focusing attention on the research of fiber reinforced rubber composites [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%